Pengaruh Persepsi Kemudahan Penggunaan, Manfaat Dan Risiko Terhadap Minat Menggunakan Uang Elektronik Di Surabaya - Hendra Prasetya; Scenda Erka Putra (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The problem examined in this study is whether the perceived ease of use, perceived benefits and perceived risk partially have asignificant effect on the interest in using electronic money in Surabaya. This study aims to determine the significance of the effect of perceived ease to use, perceived benefits and perceived risk of interest in using electronic money in Surabaya. There are three independent variable studied, namely perceived ease to use, perceived benefits and perceived risk. The dependent variable is interest in using. The population is people in Surabaya who know electronic money. Determination of the sample using purposive sampling with criteria at minimal 18 year old and using electronic money. The number sample processed was 94 samples. The analysis technique uses multiple linear regression analysis. The hypothesis testing using t test. The result is that perceived ease of use and perceived benefits partially have a significant positive effect and risk perception has a significant negative effect on interest in using electronic money in Surabaya. The implication is that electronic money issuers should continue to innovate electronic money by increasing or adding service features found in application on smartphones and making their operation easier and opening more places to fill electronic money. Public understanding of electronic money needs to be improved again.